Pengaruh Capital Intensity dan Inventory Intensity terhadap Tax Avoidance pada Perusahaan Otomotif di BEI - Wahyuni, Putri (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to determine the effect of capital intensity and inventory intensity on tax avoidance in automotive and component sub-sector manufacturing companies listed on the Indonesian Stock Exchange. This research method uses quantitative data types and data sources are secondary data sources. The unit of analysis and observation in this study is the automotive and component sub-sector manufacturing companies listed on the Indonesian Stock Exchange with a population of 13 companies. From the population, selected using purposive sampling technique and obtained as many as 9 companies for 5 periods, namely the period 2018 - 2022, totaling 45 samples. The results of the study partially show that capital intensity has a tcount value <ttable with a value of 1.366 <2.02269 and a significant value> 0.05, namely with a value of 0.180> 0.05, inventory intensity has a tcount value> ttable with a value of 7.055> 2.02269 and a significant value <0.05, namely with a value of 0.000 <0.05. The results of the study simultaneously show that capital intensity and inventory intensity have a value of Fcount> Ftable with a value of 97,573> 3.24 and a significant value of <0.05, namely 0.000 <0.05. The coefficient of determination (R Square) is 0.837 or 83.7%, which means that the tax avoidance variable can be explained by capital intensity and inventory intensity, the rest is 16.3%, the tax avoidance variable can be explained by other variables not examined in this study such as leverage, sales growth, company size, corporate social responsibility disclosure.